Developing porous microspheres for water treatment applications - Samad, Sabrin Abdus (2022)
Water pollution produced by micropollutants has increased in recent decades posing a significant threat to environment and human development. This has fuelled the need for cost effective and sustainable water treatment options to meet demand. Existing porous materials used for wastewater treatment are manufactured based on synthetic approaches which requires use of expensive and or toxic chemicals, long processing time and expensive manufacturing approach. Hence, developing adsorbents using simple, rapid synthesis pathways and with a reduced environmental footprint are still challenging. The principal focus in this thesis was to develop systematic and robust manufacturing of porous materials using flame spheroidisation process which excludes the use of these expensive and toxic chemicals during manufacturing. To date, no research has demonstrated the use of flame-spheroidised porous microspheres for wastewater treatment. As a proof of concept, porous phosphate-based glass (PBG) microspheres developed using flame spheroidisation process were explored for dye removal from water. The porosity levels of PBG microspheres were optimised by exploring the manufacturing process parameters for enabling enhanced and successful separation of micropollutants from water. Organic dye was used as a target contaminant for exploring the separation capability of the porous structure manufactured. The second part of this work involved transferring this proof-of-concept processing method to manufacture porous microspheres, particularly environmentally friendly, low-cost materials such as waste recycled glass and naturally occurring magnetite with suitable micropollutant removal capacities. In the preliminary studies, 45-63 µm porogen were used to fabricate porous microspheres from phosphate-based glass (PBG) via flame spheroidisation technique. The influence of starting phosphate glass particle size and varied porogen ratios were investigated for optimising the surface area and porosity profile of phosphate-based glass (PBG) microspheres suitable for removing Acid Red 88 (AR88) dye from water. 16 different batches of microspheres were prepared that fall under size range of 125-355 µm. The surface and cross-sectional morphological properties of the microspheres were investigated by scanning electron microscopy (SEM) and mercury intrusion analysis, which revealed the surface pores to be 5-45 µm with interconnected porosity of the microspheres manufactured. This study has also shown that use of higher porogen ratios provided with more interconnected porosity. The greatest surface area (0.54m2 /g) was achieved for 125-150 µm (size S) microspheres in the BET surface area analysis (using Kr gas). The porous microspheres with greater surface area gave better batch adsorption profile compared to microspheres with less surface area. To further improve the adsorption property of porous PBG microspheres, the influence of smaller size porogen (≤5 µm) followed by heat-treatment was investigated. Use of smaller porogen followed by heat-treatment caused further pore narrowing with the pore size distribution analysis revealing a shift from macropore to mesopores (2-50 nm), giving a surface area recorded 1.33 m2/g (using N2 gas) for microsphere heat treated at 520°C. The effect of heat-treatment (125 mg/g) demonstrated significant differences in the adsorption studies compared to non-heat-treated microspheres (83 mg/g). This improved adsorption capacity was ascribed to several factors such as increased surface area, open and interconnected porosities, surface charge, presence of porogen and presence of crystalline phases. Furthermore, enhanced column adsorption capacity was observed for heat-treated microspheres which was attributed to the unique geometry and microstructure that provided sufficient residence time for the dye molecules to diffuse into the porous structure. The dye interaction with surface of the microspheres were observed via electrostatic interaction, hydrogen bonding and Lewis acid‐base interaction without any internal or external functionalisation of the microspheres. This study also showed successful manufacture of porous recycled glass microspheres (PRGMs) using a revised methodology considering higher viscosity profiles and melt temperatures of recycled glasses (RG) compared to PBG. In this method, porogen/RG glass mixtures were ground at different time and speed (300 and 500 rpm, for 1 to 15 min.) and mixed with 2% poly vinyl alcohol (PVA) and made into 3D globules (RG-Granular) for spheroidisation. The surface area, porosity and pore size distribution were influenced by the grinding time, grinding speed and porogen to glass particle ratio. Increasing grinding time and porogen ratio revealed an increased specific surface area (from 0.03 to 7.6 m2 /g) of PRGMs retaining 63-65 % porosity. The large and smaller pore diameter of the microspheres ranged from 5.00-0.45 µm and 0.45-0.02 µm, respectively. Results have shown that removal of AR88 and methylene blue (MB) by PRGMs is influenced by pH of dye solution, porogen ratio during PRGMs manufacturing, PRGMs dose, and dye concentrations. In batch process, adsorption and coagulation process was observed for AR88 dye removal whilst MB dye removal capacity was attributed to only adsorption process. The maximum monolayer adsorption capacity (qe) recorded for AR88, and MB were 78 mg/g and 20 mg/g, respectively. XPS and FTIR studies further confirmed that the adsorption process was due to electrostatic interaction and hydrogen bond formation. Column adsorption data for PRGMs were fit best with the Yoon-Nelson and Thomas models. Based on the Thomas model, the calculated adsorption capacities at flow rate 2.2 ml/min and 0.5 ml/min were 250 mg/g and 231 mg/g, respectively which were much higher than batch scale Langmuir qe values. It was suggested that a synergistic effect of adsorption/coagulation followed by filtration process was responsible for showing higher adsorption capacities. Furthermore, PRGMs possess high recyclability, and can be directly applied to the next cyclic experiment with nearly similar dye removal efficacy. This study also demonstrated successful manufacture of porous magnetitic microspheres (PMMs) with the potential for wastewater treatment applications. In addition, XRD and MLA investigations revealed the existence of Ca2Fe2O5 brownmillerite mineral in PMMs, confirming a noble single route synthesis utilising the flame-spheroidisation method. Grinding time and the porogen to magnetite particle ratio had an impact on total porosity and pore size distribution. The number of pores and surface area increased when the grinding time and porogen ratio were increased. The surface area of PMMs increased from 0.02 ± 0.01 m2/g for magnetite particles to 4.70 m2/g ± 0.01 for PMMs ground for 15 minutes with a 1:3 porogen ratio. The adsorption kinetics of AR88 and MB using unwashed and washed PMMs revealed complete adsorption within 360 mins for all dye concentrations. The maximum monolayer adsorption capacity calculated for UW-PMMs and W-PMMs were 80 mg/g and 50 mg/g respectively for AR88 and 14.5 mg/g and 6 mg/g respectively for MB. The interaction of MB dye with PMMs was primarily caused by a combination of variables including surface area, phase structure, surface hydroxyl density, surface charge, and possible photoactivity. However, more work required to investigate the possible photocatalytic activity of the Ca2Fe2O5 which would be a potential area of research for future work.